Perancangan Sub Sistem Pendeteksi Warna Pada Automatic Water Filling Machine Menggunakan Arduino Berbasis Programmable Logic Controller - Muhammad, Fauzan Nur Akbar; Latifa, Ulinnuha (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to design a color detection sub-system on an automatic water filling machine as part of a system that can increase effectiveness and efficiency in the process of producing packaged beverages in the home industry. This study involved the use of color sensors to detect bottle color. The methods used in this study included designing a color detection sub-system, implementing appropriate color sensor technology, and testing to measure the accuracy of color detection and bottle filling. The data obtained from the test is then analyzed to evaluate the performance of the sub-systems. The results showed that the color detection sub-system on the automatic water filling machine achieved a color detection and filling accuracy rate of 94.3%. This shows that this sub-system can effectively and efficiently detect bottle color with high accuracy, and regulate the filling process appropriately.